In Situ Visualization of the Local Photothermal Effect Produced on α-Cyclodextrin Inclusion Compound Associated with Gold Nanoparticles - Silva, Nataly (Nanoscale Res Lett, 2016)
Evidence of guest migration in α-cyclodextrin-octylamine (α-CD-OA) inclusion compound (IC) generated via plasmonic heating of gold nanoparticles (AuNPs) has been studied. In this report, we demonstrate local effects generated by laser-mediated irradiation of a sample of AuNPs covered with inclusion compounds on surface-derivatized glass under liquid conditions by atomic force microscopy (AFM). Functionalized AuNPs on the glass and covered by the ICs were monitored by recording images by AFM during 5 h of irradiation, and images showed that after irradiation, a drastic decrease in the height of the AuNPs occurred. The absorption spectrum of the irradiated sample showed a hypsochromic shift from 542 to 536 nm, evidence suggesting that much of the population of nanoparticles lost all of the parts of the overlay of ICs due to the plasmonic heat generated by the irradiation. Mass spectrometry matrix-assisted laser desorption/ionization-time-of-flight (MALDI-TOF) performed on a sample containing a collection of drops obtained from the surface of the functionalized glass provided evidence that the irradiation lead to disintegration of the ICs and therefore exit of the octylamine molecule (the guest) from the cyclodextrin cavity (the matrix). [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-016-1322-z) contains supplementary material, which is available to authorized users.